Iranian Christian Converts in Malaysia - Nuei, Gholamreza; Ahmad Shah, Faisal (Jurnal Usuluddin, 2018)
In a majority of Muslim countries, the number of Muslims converting to other religions is not documented. This study investigates a group of Iranians residing in Malaysia, who have converted to Christianity. This article focuses on this subgroup of ex-Muslims to explore the reason of conversion. The data was collected in Kuala Lumpur, Malaysia. We carried out the study through in-depth interviews with 13 people; also, 45 people answered a (quantitative) questionnaire. The research findings revealed some of the typical religious, social and personal reasons behind the conversion of this group of “ex-Muslims.” The contribution of their Islamic knowledge (including, qur’anic and ḥadīthī) also will be assessed.